Assessment of economic activity of the company on the base of fuzzy inference rules - Chojnacki, Andrzej; Borzęcka, Hanna (Studia Informatica. System and information technology, 2009)
The article presents the assessment of companies efficiency, the idea based on the fuzzy set theory and fuzzy logic. Relevant financial measures are selected by experts and auditors. Variables of the proposed fuzzy model are expressed as linguistic variables and their correlations are defined by If-Then fuzzy rules of conclusion. The theoretical modeling is then followed by numerical examples. There is further extension of model toward assessment and comparison for enterprises of different size and various business branches.